Determinanty rozwoju regionalnego na przykładzie województwa lubelskiego - Chojnacki, Piotr (The Determinants of Regional Development Basing Upon Lublin Region, 2007)
The paper concerns an analysis of regional conditions which delimit the level of Lublin region economic development. The analysis points to the specificity of Lublin region regarding factors which do not, exist in other regions with similar intensity and are not decisive of other regions' economic specificity. These factors are as follows: low population density, low urbanization level, high share of low-commodity and low-input agriculture, marginalization of both industry structure and economic value of region, high ecological value of natural environment in region. The factors characterized in the paper create both barriers and developing perspectives of region.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 165-173